Warunki wstępne interpretacji doświadczenia religijnego. Pomiędzy »logos spermatikos« a »qehal el« - Kotkowska, Elżbieta (Wydział Teologiczny UAM 2008, 2008)
Nowadays we observe social transformations that have no counterparts in previous ages. Social dependences are expressed in forms that change and increase with unprecedented intensity. Human beings in their individual experience, particularly religious, realize themselves through dynamic relations to the surrounding world, other people and God. People desire a deepened interpretation what they experience. In this article I seek research tools which can help investigations in the area of fundamental theology which is expected to transform or translate individual experience in a rational way into an objective interpretative pattern. We seek such models of reality, which will ground theological investigations in the social relation of an individual person to world [in general] and to transcendence. Two investigative categories from the Christian tradition are accepted in the article: logos spermatikos and assembly of God – qehal which especially take into account the salvific perspective of the history of creation. These notions allow us to describe phenomena not only as static; they also allow us to interpret dynamic relations underway in our time. In the accepted investigative model (model 2) both the beginning and the aim of creation are qualified as dynamic realities. They influence and react to everything that happens in creation. We should therefore interpret the precondition of individual religious experience as dynamic. This will let us describe the .transient relations. as a basis in these investigations. Such an approach will prevent us from deprecating individuality in favor of the community, or the reverse.
Initial Conditions of the Interpretation of Religious Experience. Between »logos spermatikos« and »qehal el«
Keywords: kategoria badawcza; research category; początek; aim; dynamika; dynamics; statyka; statics